Information Systems Inventory of Goods in The Warehouse at PT. Transvision - Khaidir Zulkhaida; Yunan Henryanto; Hasan Jaenuddin (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2021)
On the other hand, the system currently running at PT. Transvision, especially in the inventory section, in data processing errors often occur delays in goods orders due to monitoring of stock items that are still done manually with the number of items available. Even if the goods that consumers are looking for are in empty stock because the delay in stock input of goods can cause sales to decline, the goods that should be able to be sold cannot be sold. The author makes a problem limitation only on the Inventory Information System at PT. Transvision Banda Aceh using Visual BASIC.NET application, which is the purpose of writing, namely to identify and design the Inventory Information System at PT. Transvision Banda Aceh. There are two methods that the author uses to collect data, namely field studies and library studies. From the results of research and observations that have been made at PT. Transvision Banda Aceh, it can be concluded that the existence of this Inventory Information System Program Information system at PT. Transvision Banda Aceh becomes precise, and accurate, especially in the inventory section. And obtain information about the inventory of these goods becomes easier and this information system is able to solve problems that often occur at PT. Transvision Banda Aceh is difficult in controlling and supervising the inventory of goods and planning the procurement of goods. This procurement information system can avoid excess inventory and overcome the scarcity of goods which is of course highly expected by business actors so that an information system program is created in order to obtain quality information.